Mobile-Based Health Service Information System at Kwala Begumit Village Health Center, Stabat - Sinulingga, Moja Syahfitri; Br Tarigan, Ita Margaretta; Br Surbakti , Asprina (JCEIT: Journal of Computer Engineering and Information Technology, 2024)
Abstract: In Kwala Begumit village, there are health centers, health clinics, and pharmacies, and the average health institution already has a computer-based information system. But there is one thing that is lacking, namely the unavailability of a mobile-based information system that integrates all health institutions in Kwala Begumit village, so it is not easy for the people of Kwala Begumit village to get integrated information from the room or doctor's practice schedule in Kwala Begumit village. Information on patient data, patient visits, Medical Records, drug data, drug procurement, drug enforcement, doctor data, and queues, can be done easily and in a relatively short time with this application, puskesmas Kwala Begumit can improve the quality of health services to the community. The application also overcomes the problem of adding data identical to the accumulation of papers and adding space for files. Keywords: Health Center System, Health Services, Mobile Based System   REFERENCES Abdullah, D., Katin, M. R., & Juhardi, U. (2023). PERANCANGAN APLIKASI VIDEO EDUKASI PENYAKIT MENULAR PADA PUSKESMAS BETUNGAN BERBASIS ANDROID. JURNAL MEDIA INFOTAMA, 19(2), 409–414. https://doi.org/10.37676/jmi.v19i2.4304 Alam, M. F. N., Ramadhan, D. N., & Tulloh, R. (2022). PEMBUATAN SISTEM INFORMASI KEBIDANAN (E-TOCOLOGIST) UNTUK PELAYANAN MONITORING KESEHATAN PADA IBU DAN ANAK BEBASIS WEBSITE DAN APLIKASI MOBILE DI KLINIK ROHAENI, S.ST. Alghofari, A. K., & Arifin, A. L. M. (2021). Sistem Informasi Manajemen Klinik Imam Syuhodo PKU Muhammadiyah Cabang Blimbing Berbasis Website. Abdi Teknoyasa, 46–52. https://doi.org/10.23917/abditeknoyasa.v2i2.312 Anamisa, M. (2020). Dasar Pemrograman WEB Teori dan Implementasi: HTML,CSS,Javascript,Bootstrap,Codelgniter. Media Nusa Creative. Andra, D., Widiyastuti, A., & Susianto, D. (2019). PENGEMBANGAN SISTEM INFORMASI REKAM MEDIS BERBASIS WEB PADA PUSKESMAS GISTING. 3. Ardilla, Y., Pramesti, S., & Astutik, I. (2020). IMPLEMENTASI SISTEM INFORMASI LAYANAN RAWAT INAP RUMAH SAKIT. Budi Santoso, A. (2022). PEMROGRAMAN WEB PHP DASAR DATABASE MYSQLI DENGAN BOOTSTRAP (Widina Bhakti Persada Bandung). Hafiz, M., Wicaksosno, T., Apriliani, E., & Haryono, W. (2022). Agile Development Methods Dalam Perancangan Aplikasi Penjualan Berbasis E-Commerce Pada Pt.Indo Gemilang Sakti. 1(6). Hikmah, N., Suradika, A., & Ahmad Gunadi, R. A. (2021). METODE AGILE UNTUK MENINGKATKAN KREATIVITAS GURU MELALUI BERBAGI PENGETAHUAN (KNOWLEDGE SHARING) (STUDI KASUS: SDN CIPULIR 03 KEBAYORAN LAMA, JAKARTA. Instruksional, 3(1), 30. https://doi.org/10.24853/instruksional.3.1.30-39 Mas, P. E. (2022). PEMROGRAMAN APLIKASI MOBILE. Cerdas Ulet Kreatif. Primadewi, Nugroho. (2022). Sistem Informasi Terintegrasi “Sistem Informasi yang mengintegrasikan data dalam lingkup Enterprise.” UNIMMA PRESS. Primin, B., & Wibowo, A. P. (2023). Implementasi Aplikasi Berbasis Mobile Untuk Pelayanan Jasa Kesehatan. Jurnal Informatika: Jurnal Pengembangan IT, 8(2), 119–125. https://doi.org/10.30591/jpit.v8i2.5076 Rochaety, E. (2019). SISTEM INFORMASI MANAJEMEN. Penerbit Mitra Wacana Media. Santoso, M. H., & Anggara, E. D. (2021). RANCANG BANGUN APLIKASI MOBILE SISTEM INFORMASI PELAYANAN KESEHATAN DI KECAMATAN PURWOKERTO TIMUR. Jurnal Informatika. Sasmito, G. W., & Wiyono, S. (2022). Transcrop: Media Pemesanan Transportasi Agribisnis Online Berbasis Web. Jurnal Informatika: Jurnal Pengembangan IT, 7(1), 8–12. https://doi.org/10.30591/jpit.v7i1.3418 Sulila, I., Lahinta, A., & Tuloli, M. S. (2020). SISTEM INFORMASI PELAYANAN KESEHATAN BERBASIS WEB PADA KLINIK GOCARE. Usnaini, M., Yasin, V., & Sianipar, A. Z. (2021). Perancangan sistem informasi inventarisasi aset berbasis web menggunakan metode waterfall. Jurnal Manajamen Informatika Jayakarta, 1(1), 36. https://doi.org/10.52362/jmijayakarta.v1i1.415 Yulianti, D, T., & Prastowo, A., T. (2021). Pengembangan Digitalisasi Perawatan Kesehatan Pada Klinik Pratama Sumber Mitra Bandar Lampung. Jurnal Teknologi Dan Sistem Informasi (JTSI), 2(2), 32–39.